UPAYA MENINGKATKAN HASIL BELAJAR SISWA DALAM MATA PELAJARAN PKN MELALUI MELALUI MODEL PEMBELAJARAN PPSI (PROSEDUR PENGEMBANGAN SISTEM INSTRUKSIONAL) PADA SISWA KELAS XII.IPS.3 SMA N 1 LEMBAH MELINTANG - Syafril Syafril (JURNAL MANAJEMEN PENDIDIKAN, 2017)
Based on study results VII.A Grade Students of SMPN 8 Padang in social studies found that student learning outcomes in social studies is still very low. The average student learning outcomes are still under KKM. The purpose of this study is to describe and obtain information about the efforts to improve student learning outcomes in subjects IPSsub human beings Describe the social and economic needs through immoral Learning Model Cooperative Learning Structures (CLS) in the Class VII.A SMPN 8 Padang Sumatra West.This research is a class act. The procedure in this research include planning, action, observation and reflection. The study consisted of two cycles of the four meetings. Subject of the study consisted of 32 students Grades VII.A SMPN 8 Padang. Data were collected by using observation sheet and daily tests. Data were analyzed using percentages.Based on the results of research and discussion that has been raised, it can be concluded that the Learning Model Cooperative Learning Structures (CLS) can improve student learning outcomes in social studies sub Describing humans as social beings in the moral and economic needs in SMPN 8 Padang. Learning outcomes of students from the first cycle to the second cycle. The results of students in the first cycle was 51.25 (Enough) increased to 84.28 (Good) with an increase of 33.03%.